O processo de territorialização da estratégia saúde da família no bairro Morrinhos-Montes Claros/MG: uma contribuição geográfica - Silveira, Iara Maria Soares Costa da (2013)
The Brazilian health has experienced significant changes with the implementation of the public health system call Sistema Único de Saúde (SUS). This system becomes a new political-institutional model. Successful experiences in some cities were building the foundation for this health policy. The city of Montes Claros contributed for this construction through the \'Project Montes Claros\'. Regionalization is an instrumental in the construction of this policy. To guide the organization, the Director Plan of Health Regionalization (PDR/MG) was established in the state of Minas Gerais. In the face of urban growth and the necessary extension of the Health System, the State and the cities adopted measures based on SUS and PDR/MG for the \' territorialisation\' of the Estratégia Saúde da Família (ESF), the strategy that organize the primary attention in health. The Geographic Science enters in this context as a tool capable of contributing to the organization of these areas of health. Thus, this study aimed to analyze about the process of territorialization and concepts used in the spatial strategies of the Family Health - FHS in Morrinhos neighborhood in Montes Claros - Minas Gerais, based on the assumptions of the NHS and guidelines outlined by the Ministry of Health , Health Department of the State of Minas Gerais and Municipal Secretary of Health of Montes Claros MG.The research was descriptive and exploratory with a qualitative and quantitative approach, anchored in literature review for understand what were the criteria used for the spatialization of ESFs in Morrinhos neighborhood. For concreteness and success of the study, in loco visits were realize, as well as desk reviews, observations, structured and semistructured interviews that resulted in construction of maps, charts, tables, graphs, and illustrations. The research showed that the ESF really are recognized in their purposes by users of the system, and that studies like that can show that geography can contribute to the organization and management of ESF spaces, and the category Territory , in their contexts, have been recommended for the propose of SUS.